FAKTOR-FAKTOR MODERATING KEUNGGULAN KOMPETITIF UMKM PADA MASA COVID-19 - Supriatin, Dyah (Sekolah Tinggi Ilmu Ekonomi Tamansiswa Banjarnegara, 2024)
ABSTRACT The economy reaps substantial benefits from the contributions of micro, small, and medium enterprises (MSMEs). Despite their pivotal role in sustaining the national economy during the 2008 global financial crisis, where they generated employment and diversified exports beyond oil and gas, MSMEs in Indonesia have faced their most severe setback with the advent of Covid-19. Navigating through market upheavals now requires the adaptability of MSMEs, given the growing consumer demand for innovative products. The competitiveness and marketing efficacy of MSMEs hinge on their market and entrepreneurial orientations. This research endeavors to ascertain the significant impact of market and entrepreneurial orientations on company performance amid the pandemic, and to what extent these orientations exert influence. A total of 104 MSME participants were involved in the study, with SEM PLS employed as the methodology. The findings underscore that a focus on the market correlates with an increased likelihood of business success. Additionally, a positive relationship exists between competitive advantage and business performance, with no moderation observed in the connections between market orientation, entrepreneurial orientation, and business performance by competitive advantage.